Binding of molecular oxygen by an artificial heme analogue: investigation on the formation of an Fe–tetracarbene superoxo complex. Issue 15 (8th March 2016) - Anneser, Markus R.; Haslinger, Stefan; Pöthig, Alexander; Cokoja, Mirza; D'Elia, Valerio; Högerl, Manuel P.; Basset, Jean-Marie; Kühn, Fritz E.
Abstract : The reactivity of a heme-like organometallic Fe–NHC complex with O2 is studied. The formation of a superoxo Fe(iii ) intermediate is observed. The reactivity of the intermediate in acetone and acetonitrile is described and the products are identified. Abstract : The dioxygen reactivity of a cyclic iron(ii ) tetra–NHC-complex (NHC: N-heterocyclic carbene) is investigated. Divergent oxidation behavior is observed depending on the choice of the solvent (acetonitrile or acetone). In the first case, exposure to molecular oxygen leads to an oxygen free Fe(iii ) whereas in the latter case an oxide bridged Fe(iii ) dimer is formed. In acetone, an Fe(iii )-superoxide can be trapped, isolated and characterized as intermediate at low temperatures. An Fe(iii )–O–Fe(iii ) dimer is formed from the Fe(iii ) superoxide in acetone upon warming and the molecular structure has been revealed by single crystal X-ray diffraction. It is shown that the oxidation of the Fe(ii ) complex in both solvents is a reversible process. For the regeneration of the initial Fe(ii ) complex both organic and inorganic reducing agents can be used.